Investigating Protein–Ligand Interactions by Solution Nuclear Magnetic Resonance Spectroscopy. Issue 8 (16th February 2018) - Becker, Walter; Bhattiprolu, Krishna Chaitanya; Gubensäk, Nina; Zangger, Klaus
Abstract: Protein–ligand interactions are of fundamental importance in almost all processes in living organisms. The ligands comprise small molecules, drugs or biological macromolecules and their interaction strength varies over several orders of magnitude. Solution NMR spectroscopy offers a large repertoire of techniques to study such complexes. Here, we give an overview of the different NMR approaches available. The information they provide ranges from the simple information about the presence of binding or epitope mapping to the complete 3 D structure of the complex. NMR spectroscopy is particularly useful for the study of weak interactions and for the screening of binding ligands with atomic resolution. Abstract : Pick your NMR : Protein–ligand interactions are of fundamental importance in almost all processes in living organisms. Solution NMR spectroscopy, which is particularly useful for studying weak interactions, offers a large repertoire of techniques to study ligand complexes, providing information ranging from the simple presence of binding or epitope mapping to the complete 3 D structure of the complex.